2021
DOI: 10.1007/s00248-021-01887-5
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Patterns from Soils in Madagascar: an Insight from Maromizaha Forest (Evergreen Humid Forest) to Outside (Deciduous Forest)

Abstract: Soil fungal diversity was studied by next-generation sequencing and compared in two different Malagasy ecosystems, the first a New Protected Area (Maromizaha NAP) that is a rich humid evergreen forest and the second a degraded and declined deciduous forest (Andaravina) whose area has been also eroded. Both areas, however, have comparable annual rainfalls and soil pH values. So it was of interest to examine the soil fungal diversity in each system and compare them. We detected 1,817,658 reads representing Ascom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…This result indicates the still little knowledge of fungi from the Madonie Park, and consequently their poor representativeness in the databases. This fact is common in places where fungal diversity has been scarcely investigated, such as Madagascar, where Ghignone et al (2021) found many unknown fungi with the same approach used in the present work.…”
Section: Core Components Of the Fungal Communitiesmentioning
confidence: 74%
“…This result indicates the still little knowledge of fungi from the Madonie Park, and consequently their poor representativeness in the databases. This fact is common in places where fungal diversity has been scarcely investigated, such as Madagascar, where Ghignone et al (2021) found many unknown fungi with the same approach used in the present work.…”
Section: Core Components Of the Fungal Communitiesmentioning
confidence: 74%
“…With the increasing amount of litter, the AMF fungal hyphae proliferate in organic substrates [68] and grow into decomposing leaf litter [69,70], suggesting that AMF fungi may represent important pathways for plant uptake of nutrients in tropical and subtropical forests. Apart from this, the tropical and subtropical rainforests are characterized by a high presence of organic matter, and they can produce more litter than other ecosystems [71]. Such conditions result in an enrichment of pathogenic and saprotrophic fungi, while symbiotic fungi are present in lower number [71] (Table 1).…”
Section: Soil Fungal Community Functionmentioning
confidence: 99%
“…Apart from this, the tropical and subtropical rainforests are characterized by a high presence of organic matter, and they can produce more litter than other ecosystems [71]. Such conditions result in an enrichment of pathogenic and saprotrophic fungi, while symbiotic fungi are present in lower number [71] (Table 1).…”
Section: Soil Fungal Community Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first scientific reports for the Funga (Kuhar et al, 2018) of Madagascar date back to the late 19th century (Cooke & Massee, 1890), followed by several studies conducted by French mycologists in the first half of the 20th century, including those of Patouillard (1924Patouillard ( , 1928, Romagnesi (1941), Métrod (1949) and Heim (1936Heim ( , 1938aHeim ( , 1938bHeim ( , 1945 (Vizzini et al, 2019). It has not been until very recently that the interest in Madagascar fungi resurfaced, with several new species being reported, monographs being published, and high-throughput environmental sequencing projects being conducted (Antonín et al, 2005;Antonín & Buyck, 2006;Aptroot, 2016;Buyck, 2008;Buyck et al, 2007;Duhem & Buyck, 2007;Eyssartier et al, 2001;Eyssartier & Buyck, 1999a, 1999bGhignone et al, 2021;Ralaiveloarisoa, 2022;Ralaiveloarisoa et al, 2020Ralaiveloarisoa et al, , 2021Shay et al, 2017).…”
Section: Introductionmentioning
confidence: 99%